2019
DOI: 10.3390/nu11081869
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Planet, Healthy Youth: A Food Systems Education and Promotion Intervention to Improve Adolescent Diet Quality and Reduce Food Waste

Abstract: Emerging evidence suggests a link between young people’s interest in alternative food production practices and dietary quality. The primary purpose of this study was to examine the impact of a student-driven sustainable food systems education and promotion intervention on adolescent school lunch selection, consumption, and waste behaviors. Sixth grade science teachers at two middle schools (n = 268 students) implemented a standards-based curriculum on sustainable food systems, addressing the environmental impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(119 citation statements)
references
References 35 publications
1
115
0
3
Order By: Relevance
“…In addition to a sedentary lifestyle, obesity is affecting a large part of the population because they do not follow the appropriate nutritional recommendations for a proper diet [3,4]. As a consequence of this worrying situation, educational centers are carrying out initiatives and training programs to encourage the promotion of dietary education with the aim of improving students' knowledge [6,7,[9][10][11] and to encourage an active and healthy life in order to reduce the possibility of suffering from certain diseases resulting from a poor diet [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a sedentary lifestyle, obesity is affecting a large part of the population because they do not follow the appropriate nutritional recommendations for a proper diet [3,4]. As a consequence of this worrying situation, educational centers are carrying out initiatives and training programs to encourage the promotion of dietary education with the aim of improving students' knowledge [6,7,[9][10][11] and to encourage an active and healthy life in order to reduce the possibility of suffering from certain diseases resulting from a poor diet [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, education plays a primary role in establishing good eating habits in people [6]. Specifically, dietary education can promote the adequate behavior of adolescents in the face of their inadequate diet [7]. In line with this, it has been observed that youths follow a diet with a high sugar content, which is detrimental to their health [8].…”
Section: Introductionmentioning
confidence: 99%
“…The very few studies addressing related questions have focused on aspects such as consumers’ willingness-to-pay for sustainable specific products (such as some organic and local foods) [ 16 , 17 ], the possible interaction between millennials and sustainability in the food sector [ 18 ], or the knowledge and awareness of general sustainability initiatives among college students [ 19 , 20 ]. Most of these studies support, as a main conclusion, the need to implement a wide range of initiatives aimed at educating consumers about sustainable dietary patterns, thus highlighting the general unawareness of the population, and a missing systematic engagement with formal education on this topic, in the community.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used nutrition promotion strategies were related to promoting healthy food choices through encouraging students to select fruit, as well as conducting taste tests, which both engage students in decision-making processes. These collaborative strategies have been found to be successful in fostering healthy choices in the lunchroom [36,37], thus providing a feasible approach to promoting high-quality nutritional consumption. Less commonly used strategies were related to asking for student input on menu planning and specific menu items.…”
Section: Discussionmentioning
confidence: 99%